Study the effect of increased levels of lead on sera alpha amylase activity, and some biochemical parameters from a large private electrical generators workers - Mehde, Atheer Awad; Yusof, Faridah; A. Mezal, Sabreen; Farhan, Layla O.; Mehdi, Wesen Adel (AENSI Publications, 2015)
Background Lead poisoning is a health condition that occur when people are showing to lead compound through inhalation, swallowing, and rarely, through the skin. Lead poisoning frequently occurs from repeated contact to small amounts of lead. Objective: The aim of the current study is to evaluate the level of the alpha amylase activity , Lead and several biochemical factors in sera workers which working to turn on and control on the large private electrical generators. Results: The group50 male employed on large private electrical generators workers, mean age (35.47 ± 5.29 years) comparing with 40 male (34.80±4.28) apparently healthy control , the result showed that serum of S. Lead ,α-amylase activity and specific activity, were significantly increase(p<0.001) in large private electrical generators workers group compared to the control group. Conclusion: Lead poisoning has serious risks to human health, and exposure to lead possibly will decrease lifespan and have health effects in the long term for these workers